1921
DOI: 10.1001/archderm.1921.02350190040004
|View full text |Cite
|
Sign up to set email alerts
|

The Viability of Ringworm Fungi in Dry Cutaneous Material

Abstract: This experiment was conducted to determine in a general way how long these fungi could remain viable in the surplus scrapings, hairs, etc., which had been preserved dry for future use in paper envelops in our laboratory files. The results would also yield some rough idea of how long the material might retain its infectiousness in those articles of clothing (slippers) and the toilet (brushes and combs) which are not always periodically cleansed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1927
1927
1979
1979

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The reason for this disappearance is hard to understand in view of the viability of the pathogenic fungi (Farley, 1921 ;Weidman, 1927a;Bruhns, Alexander, and Kadisch, 1929), but the secondary bacterial contamination which sometimes occurs may in some way exert a lethal influence on the moulds. In this connexion the observations of Weidman (1926) on a case of pedal ringworm sown with yeasts are of importance.…”
Section: Difficulties In Diagnosismentioning
confidence: 99%
“…The reason for this disappearance is hard to understand in view of the viability of the pathogenic fungi (Farley, 1921 ;Weidman, 1927a;Bruhns, Alexander, and Kadisch, 1929), but the secondary bacterial contamination which sometimes occurs may in some way exert a lethal influence on the moulds. In this connexion the observations of Weidman (1926) on a case of pedal ringworm sown with yeasts are of importance.…”
Section: Difficulties In Diagnosismentioning
confidence: 99%
“…Many researchers have shown that dermatophytes remain viable at room temperature for extended periods of time in infected skin, hair, and nails (5,8,9,11,13,14,16,17,19). In this study we attempted to determine the effect of storage temperature on the viability of Trichophyton mentagrophytes in infected guinea pig skin scales in a quantitative and controlled manner which was not generally used in previous investigations.…”
mentioning
confidence: 99%